Enhancing Speaking Motivation Through Duolingo and NLP Presupposition: "There Is No Failure, Only Feedback" - Ruthertati Sianturi; Juniar Elfrida Sitohang; Rita Hartati (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Speaking skills in English are essential in the era of globalization; however, many learners still face challenges due to low motivation, lack of confidence, and fear of making mistakes. This study aims to analyze how the integration of the Duolingo application and the Neuro-Linguistic Programming (NLP) presupposition “There is no failure, only feedback” can enhance students’ motivation in speaking English. This research employs a qualitative approach through literature review and a survey conducted with 30 Duolingo users. The results show that 83.3% of respondents felt more enthusiastic, 90% felt more confident, 83.3% experienced significant benefits from the NLP principle, and 93.3% felt more motivated after using the combination of Duolingo and the NLP principle. Additionally, 93.3% of respondents also recommended combining these two approaches to other learners. Open responses from participants indicated that Duolingo provided a fun learning environment, while the NLP principle helped them overcome the fear of making mistakes. The discussion highlights that the synergy between enjoyable technology-based learning and a psychological approach that fosters a positive mindset towards mistakes significantly contributes to creating a supportive learning environment. These findings indicate that an approach combining learning technology and positive thinking is highly effective in helping students speak English without fear of making mistakes.